Reservoir Induced Seismicity at the Laúca Dam in Northwestern Angola - Focal Mechanisms and Stress Field Estimation - Schirbel, Lucas Alexandre (2023)
Reservoir Triggered Seismicity (RTS) is a well documented phenomenon, with over 100 cases reported worldwide. The impounding of water reservoirs changes the local stress field and serves as a catalyst/trigger for the release of tectonically accumulated stress. RTS cases occurring in intraplate regions are particularly interesting, since they provide an opportunity to study the local and regional stress field in areas where earthquake occurrences are rare and these chances seldom come by. We report a new case of RTS in southwestern Africa, in the Kwanza basin, Malanje province of Angola, located in the Angolan Shield. The Lauca reservoir, where seismicity is taking place, sits atop a region composed mainly of granitic and gneissic rocks covered by a thin layer of sedimentary rocks, and seismicity there was observed shortly after the water level rose to about 90m following initial impoundment. The maximum dam height is 156m and the reservoir volume is 5,044.85 Hm3. Over 270 events were detected between March/2018 and and November/2020, and seismicity has not ceased, indicating both initial and protracted seismic activity at play. The frequency of events with magnitude larger than 2.5 ML has increased over time. The largest event so far had magnitude 3.0 ML, and was felt in nearby villages and towns. P and S phases for all events were manually picked, and a composite Wadati diagram yielded a Vp/Vs ratio of 1.710 +- 0.003 for the lake area, compatible with the local geology. We use minimization of travel time residuals with both HYPO71 and HYPOCENTER to determine the best half-space velocity model for the reservoir area, which we determine to be Vp= 6.1 km/s. Back Azimuth angles for all events were also manually determined and used to better constrain locations. Epicentral locations show that most events cluster along two roughly N-S oriented faults, an uncommon pattern in cases of RTS, but which can nonetheless aid the determination of the focal mechanisms. We determine focal mechanisms for four of the largest events in the area using both P and SH arrival polarity and P/S amplitude ratios, and compare it to models of the regional stress field. We find that the faulting regime in the area is transpressive and that SHMax points in the SW-NE direction, in disagreement with current geodynamical models of the Nubian plate.